Impediments To Muslim Girl-Child Education In Ghana: The Case Of Nima In The Greater Accra Region - Mustapha Abdullah Kuyateh (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Girl child education is a significant contributory factor to economic development and a key to sustainable development. In an era of globalization, the education of the girl child is considered a strategic investment in human and intellectual capital. However, the contextual realities for girl children and the state of their education in Nima are daunting, such that Young-Muslim girls who are supposed to be in school are either sent off in marriages or made to help in business activities at the expense of schooling. Analyses of the Ghana Education Service (GES) Report (2005) indicates that GES is much interested in the high enrolment in the basic schools but silent on the retention and sustainability of these laudable programs (GES 2005). Also, in spite of the ongoing efforts lots of girls are still out of the classrooms and gender parity remains a far cry nationally and especially in some parts of Ghana (GES 2008). What accounts for these persistent imbalances? Of course, the ongoing efforts are necessary but are they sufficient? What are the impediments and how might they be overcome? This research work explores these questions through a case study of Nima in the Greater Accra Region of Ghana.